The Relationship Of Intellectual Capital Disclosure On Financial Statements Of Plantation Companies On Tax Paying Compliance - Raya Puspita Sari Hasibuan; Anita Putri; William Caesar (International ABEC, 2021)
The long-term goal of implementing this research is to determine the relationship between the independent variable and the dependent variable and the existence of moderating variables that can strengthen or weaken the relationship between these variables. Where the independent variables in this study are the application of accounting conservatism, firm size, firm age, concentration of ownership and independent commissioners, while the dependent variable is tax compliance and the moderating variable is intellectual capital disclosure. The object of this research is all plantation companies whose financial statements have been audited from 2016-2020 and are listed on the Indonesia Stock Exchange. The analytical tool used in this research is SmartPLS. This research was conducted by downloading the financial statements of the plantation companies on the IDX website, namely www.idx.co.id. The number of companies that were sampled in this study were 75 plantation companies according to predetermined criteria. The result of this study is that all the independent variables contained in this study have no effect on the dependent variable, meaning that there is a discrepancy between the theory previously described and the results of this study. While the moderating variable in this study was able to strengthen the relationship between the dependent variable and the independent variable. Thus the results of this study need to be evaluated better with respect to the use of appropriate variables, suitability of the use of analytical tools, as well as the object under study.